Molecular basis for the calcium-dependent activation of the ribonuclease EndoU - Florian Malard; Kristen Dias; Margaux Baudy; Stéphane Thore; Brune Vialet; Philippe Barthélémy; Sébastien Fribourg; Fedor V. Karginov; Sébastien Campagne (Nature Communications)
Abstract Ribonucleases (RNases) are ubiquitous enzymes that process or degrade RNA, essential for cellular functions and immune responses. The EndoU-like superfamily includes endoribonucleases conserved across bacteria, eukaryotes, and certain viruses, with an ancient evolutionary link to the ribonuclease A-like superfamily. Both bacterial EndoU and animal RNase A share a similar fold and function independently of cofactors. In contrast, the eukaryotic EndoU catalytic domain requires divalent metal ions for catalysis, possibly due to an N-terminal extension near the catalytic core. In this study, we use biophysical and computational techniques along with in vitro assays to investigate the calcium-dependent activation of human EndoU. We determine the crystal structure of EndoU bound to calcium and find that calcium binding remote from the catalytic triad triggers water-mediated intramolecular signaling and structural changes, activating the enzyme through allostery. Calcium binding involves residues from both the catalytic core and the N-terminal extension, indicating that the N-terminal extension interacts with the catalytic core to modulate activity in response to calcium. Our findings suggest that similar mechanisms may be present across all eukaryotic EndoUs, highlighting a unique evolutionary adaptation that connects endoribonuclease activity to cellular signaling in eukaryotes.